A new Pigmy Armadillo from the late Miocene (Chasicoan Stage/Age) of San Juan Province (Argentina) - Barasoain Goñi, Daniel (2019)
Zaedyus pichiy Desmarest, 1804, referred as pygmy or dwarf armadillo, is a Euphractinae (Xenarthra Cingulata) widely distributed in central-southern Argentina. The fossil record of this genus is well known since the Early-Middle Pleistocene. Prozaedyus Ameghino, 1891 was recognized remarking the evident morphological resemblance of the dorsal carapace respect to Zaedyus. From a phylogenetic point of view, Prozaedyus has been interpreted as an early diverging Euphractinae, restricted to the Late Oligocene and Early Miocene levels (Deseadan to Friasian SALMAs). We report here a new and particular specimen (MSJ-317) coming from the Late Miocene (Loma de Las Tapias Formation, Chasicoan Stage/Age) of the Province of San Juan, which represents a new species of Prozaedyus. The specimen includes an almost complete skull with complete dental series, some articulated fragments of the dorsal carapace and several isolated fixed and mobile osteoderms. Dental formula, ornamentation pattern of fixed osteoderms and presence of small foramina in the posterior and lateral margins of osteoderms are some of the characters that allow its inclusion within the genus Prozaedyus. Differences with known species include size (ca. 40% smaller), cranial characters (e.g., position of theinfraorbital foramen, skull bones sutures, morphology of the occipital condyles), and ornamentation pattern of mobile osteoderms. This record extends considerably the biochron of the genus up to Late Miocene. The phylogenetic analysis carried out supportits relationas a sister group of the other Prozaedyus species, and also reveals an ancient divergence of the analyzed lineage that occurs before that of the Late Oligocene-Early middle Miocene forms.